THE EFFECTIVENESS OF ISLAMIC COUNSELING SERVICES WITH THE AL-MUROQABAH TECHNIQUE TO IMPROVE THE MANNERS OF STUDENTS TO TEACHERS - Harahap, Mawadda; Nasution, Fauziah (LP2M IAI Al-Khairat Pamekasan, 2025)
This study aims to test the effectiveness of Islamic counseling services with the al-muroqabah technique in improving the manners of students to teachers at MTs Negeri 2 Medan. Referring to the phenomenon of declining students' respectful attitudes, this technique is used as a spiritual approach to foster awareness that Allah SWT is always watching human behavior. The research uses a quantitative approach with a one-group pretest-posttest design. The results of the pretest were obtained by 8 students who were indicated to have poor manners. Data were obtained through questionnaires, observations, interviews, and documentation. The results of the Wilcoxon test showed a significant improvement (p = 0.012), from the low to high manners category after the intervention. These findings confirm the effectiveness of the al-muroqabah technique in forming a polite, respectful, and obedient attitude in students through spiritual strengthening. Therefore, this technique is recommended to be integrated in Islamic counseling services in madrassas in order to build the character of students as a whole.